Ichthyofaunal diversity in snow-fed Mardi Stream of Gandaki River, Central Nepal - Neeti Chapagain; Naresh Pandey; Prabha Chitrakar (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Chapagain N, Pandey N, Chitrakar P. 2021. Ichthyofaunal diversity in snow-fed Mardi Stream of Gandaki River, Central Nepal. Biodiversitas 22: 2940-2948. This study assessed site-wise and season-wise diversity and investigated the potential environmental correlates of ichthyofaunal assemblage in snow-fed Mardi Stream of central Nepal by extensive fieldworks from June 2018 to April 2019. The ichthyofaunal diversity and community structure in the hill streams of the Nepal Himalaya are understudied. A total of 1850 individual fish belonging to 3 orders, 3 families, 9 genera, and 10 species were collected. Cypriniformes emerged as the most species-rich order, accounting for 92.6% of the total species. Based on Similarity Percentage (SIMPER) analysis, the major contributing species were Schizothorax richardsonii (27.58%), Garra annandalei (26.3%), and Naziritor chelynoides (10.82%). Diversity indices were found higher in summer season and downstream areas. Results from Generalized Linear Model (GLM) and Canonical Correspondence Analysis (CCA) revealed that pH, Dissolved Oxygen (DO), water temperature and water velocity had significant relationship with fish assemblages. The fish assemblages along the gradient of the stream may be interrupted due to climate factors and anthropogenic disturbances. This study provides baseline data on hill stream fishes of Mardi Stream which might be helpful for implementation of conservation approaches.